Effect of phytic acid as an endodontic chelator on resin adhesion to sodium hypochlorite-treated dentin - Mohannad Nassar; Noriko Hiraishi; Md. Sofiqul Islam; Maria JRH. Romero; Masayuki Otsuki; Junji Tagami (Restorative Dentistry & Endodontics)
ObjectivesPhytic acid (IP6), a naturally occurring agent, has been previously reported as a potential alternative to ethylenediaminetetraacetic acid (EDTA). However, its effect on adhesion to sodium hypochlorite (NaOCl)-treated dentin and its interactions with NaOCl have not been previously reported. Thus, in this study, the effects of IP6 on resin adhesion to NaOCl-treated dentin and the failure mode were investigated and the interactions between the used agents were analyzed.Materials and MethodsMicro-tensile bond strength (µTBS) testing was performed until failure on dentin treated with either distilled water (control), 5% NaOCl, or 5% NaOCl followed with chelators: 17% EDTA for 1 minute or 1% IP6 for 30 seconds or 1 minute. The failed specimens were assessed under a scanning electron microscope. The reaction of NaOCl with EDTA or IP6 was analyzed in terms of temperature, pH, effervescence, and chlorine odor, and the effects of the resulting mixtures on the color of a stained paper were recorded.ResultsThe µTBS values of the control and NaOCl with chelator groups were not significantly different, but were all significantly higher than that of the group treated with NaOCl only. In the failure analysis, a distinctive feature was the presence of resin tags in samples conditioned with IP6 after treatment with NaOCl. The reaction of 1% IP6 with 5% NaOCl was less aggressive than the reaction of the latter with 17% EDTA.ConclusionsIP6 reversed the adverse effects of NaOCl on resin-dentin adhesion without the chlorine-depleting effect of EDTA.